Effects of Relative Humidity on Impregnated Filters Used in Measurement of Airborne Sulfur Dioxide. Issue 7 (6th July 2019) - Chien, Chih-Hsiang; Zhou, Chufan; Sing, Simon Yang; Lopez, Benjamin; Theodore, Alexandros; Wu, Chang-Yu; Birky, Brian K
Abstract: Impregnated filters treated with alkali and humectant were first used as collection media to assess occupational exposure to sulfur dioxide (SO2 ), as outlined in the National Institute for Occupational Safety and Health Method 6004 in 1979. Since then, updated treatment protocols have been proposed with decreased amounts of alkali and glycerol, which claim the same filtering capacity. However, there has been no report on how the collection of SO2 on such impregnated media is influenced by relative humidity (RH). This study investigated the role of glycerol (G) amount on impregnated filters (G2 and G10, referring to 2 and 10% glycerol, respectively) in the collection of SO2 (100 l of 10 ppm at 1 l per minute) under low, medium, and high RHs. The testing results show that RH significantly impacted G2 filters with respect to breakthrough time, capacity, and recovery. At low RH, the 5% breakthrough time was less than 10 min and its recovery was merely 42%; at medium and high RHs, although the recovery was satisfactory, the 5% breakthrough time was still less than 100 min. By contrast, G10 filters illustrated nearly 100% recovery and evaluation by analysis of variance showed no significant effect of RH on recovery. In summary, the current treatment protocol of 2% glycerol leads to a significant underestimation of the exposure to SO2 in a low-RH environment; increasing the glycerol content can be an effective alternative to compensating for the effect of RH.